Ambivalence among University students - براء محمد حسن (College of Education for Women, 2019)
The current research was aimed at the following: 1. Measurement the Ambivalence among University students. 2. Identify the differences in Ambivalence among University students according to variable of Specialization (scientific / literary). To achieve this aims of the research, the researcher set up the instrument is scale of Ambivalence that consistent (19) item. And the researchers applying this scale on the sample amounted to (200) among University students. Then after data processing statistically, the researchers reached the following results: 1. University students have Ambivalence. 2. There is no is differences in Ambivalence among University students according to variable of Specialization (scientific / literary). In light of the results of this research the researchers came out with a number of recommendations and suggestions.